Secular trends in cranial chord variables: a study of changes in sexual dimorphism of the North Indian population during 1954-2011 - Vineeta Saini (Taylor & Francis Group, 2019)
Background: Sex estimation of fragmentary remains is a critical problem which is further aggravated by the changing pattern of sexual dimorphism due to temporal/secular changes. Previously cranial chord variables were examined only to deduce cranial abnormalities and hominin evolution. In forensic anthropological literature to date, no studies have examined the importance of cranial chord variables in sex determination and neither have secular changes been reported in those measurements to date. Aim: The present study aims to examine the sexual dimorphism and temporal changes in chord measurements in the Indian population and to provide updated sex discriminant formulae. Subjects and methods: A total of 483 (contemporary: n = 158; sub-recent: n = 325) adult crania (18-70 years) from two temporally distinct North Indian populations were included in the study. Seven chord variables were measured and data were subjected to discriminant function analysis using SPSS 16.00. Results: Analysis of the data using the t-test demonstrated significant sexual and population variations over time. Univariate discriminant analysis revealed the glabella-bregma chord as the best variable in both populations (78.5 and 74.5% accuracy in the contemporary and sub-recent populations, respectively). Using multivariate analysis classification accuracy reached 86.1% in the contemporary sample. Conclusion: It is concluded that Indian crania are going through secular changes as the contemporary population has larger chord dimensions than their predecessors and chord variables can be applied for sex estimation in the Indian population.